2004
DOI: 10.1086/381898
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐Like Receptor 4 Is Critical to Innate Host Defense in a Murine Model of Bordetellosis

Abstract: Bordetellae are important respiratory pathogens that cause pertussis (whooping cough) in humans and analogous diseases in domestic and wild animals. Immunity to Bordetella is poorly understood, in particular the early innate immune responses that contribute to inflammation, pathology, and the subsequent generation of adaptive immunity. Using B. bronchiseptica, which naturally infects mice, we show that Toll-like receptor-4 (TLR4) is required for cytokine responses to this pathogen's lipopolysaccharide (LPS) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 15 publications
5
55
0
Order By: Relevance
“…Interestingly, the bacterial burden was exacerbated in IL-17 2/2 mice, although not as significantly as in IL-1RI 2/2 mice, suggesting that some, but not all, of the effects of IL-1b involve induction of IL-17 production. These findings are consistent with the well-established role of IFN-g (4, 36) and other effector cells and molecules, such as those induced through TLR4-activation (5,42,43), in protection against B. pertussis and suggest that Th1 and Th17 cells may cooperate to mediate bacterial clearance. Consistent with previous reports on other toxins (22,23), we found that the pore-forming activity of CyaA was essential for promoting IL-1b via activation of the inflammasome in a process that involves a reduction in intracellular potassium The Journal of Immunologylevels.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the bacterial burden was exacerbated in IL-17 2/2 mice, although not as significantly as in IL-1RI 2/2 mice, suggesting that some, but not all, of the effects of IL-1b involve induction of IL-17 production. These findings are consistent with the well-established role of IFN-g (4, 36) and other effector cells and molecules, such as those induced through TLR4-activation (5,42,43), in protection against B. pertussis and suggest that Th1 and Th17 cells may cooperate to mediate bacterial clearance. Consistent with previous reports on other toxins (22,23), we found that the pore-forming activity of CyaA was essential for promoting IL-1b via activation of the inflammasome in a process that involves a reduction in intracellular potassium The Journal of Immunologylevels.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings show that CyaA induces DC maturation through TLR4 signaling and that the CTL induction by CyaA-OVA is strongly affected in TLR4-deficient mice, supporting a critical role for this pathway in the efficiency of this vector. Interestingly, it has been shown that TLR4 is a central player in orchestration of very early innate defense against B. pertussis (29) and is required for the induction and effector phases of adaptive immunity to B. pertussis (30)(31)(32). However, in these studies, TLR4 signaling was attributed to the presence of B. pertussis LPS.…”
Section: Discussionmentioning
confidence: 98%
“…Our data also suggest that plrS mutants are more susceptible to innate immune mechanisms that function at early stages of infection, perhaps by enhanced clearance by phagocytic cells. Bordetella can interact directly with macrophages (26,28), and previous work using B. bronchiseptica infection of murine lungs has shown that bacterial clearance involves activation of Tolllike receptor 4 and CD11b immune cell signaling pathways (39,50). An important next step in characterization of plrS function will include an evaluation of its contribution to immune cell activity, and toward this end, we have observed that the levels of adherence of plrS mutants to J774 macrophage-like cells in culture are similar to those of wild-type B. bronchiseptica (K. T. Cochran and S. M. Julio, unpublished observations), suggesting that the defect present in plrS strains may exist at a level other than direct interactions with immune cells.…”
Section: Discussionmentioning
confidence: 99%